The XtreemFS architecture-a case for object-based file systems in Grids - Hupfeld, Felix; Cortes, Toni; Kolbeck, Björn; Stender, Jan; Focht, Erich; Hess, Matthias; Malo, Jesus; Marti, Jonathan; Cesario, Eugenio (Concurrency and computation, 2008)
In today's Grids, files are usually managed by Grid data management systems that are superimposed on existing file and storage systems. In this paper, we analyze this predominant approach and argue that object‐based file systems can be an alternative when adapted to the characteristics of a Grid environment. We describe how we are solving the challenge of extending the object‐based storage architecture for the Grid in XtreemFS, an object‐based file system for federated infrastructures. Copyright © 2008 John Wiley & Sons, Ltd.